Peranan matriks metaloproteinases pada lesi karies dentin Matrix metalloproteinase in caries dentine lesion - Fajriani Fajriani (DiscoverSys Inc., 2012)
Matrix metalloproteinase (MMP) is a component extracelluler of matrix hydrolised which has an important role inthe process of biology and pathology. MMP has also a role in deficiency of dentine organic matrix due todemineralization by bacterial acid and tooth caries development or controlling. MMP in host originates from salivaand dentin. Saliva penetrate on the open dentinal lesion, and MMP in saliva had direct access to dentinedemineralization. It has been said that MMP saliva derived have a role in organic matrix destruction. Dentinalmatrix degradation is supposed acted by bacteria enzyme. It was clear that the cause of dentinal matrix degradationis MMP-2 and MMP-9 in gelatinolitic process, and MMP-8 in collagenitic process. This paper was aimed to explainabout enzyme that has an important role in dentine caries.